Collaborative problem-based learning in mathematics: A cognitive load perspective - Ahmad Tarmizi, Rohani; Bayat, Sahar (Elsevier, 2012)
Mathematics educators have struggled to improve learners’ performance in mathematics. Based on the cognitive load theory, many conventional instructional formats are less than effective because little consideration is given to the concept of cognitive processing capacity. Thus, investigation into problem-based learning (PBL) has been undertaken. This study examined the effects of PBL on educational statistics course. Six PBL modules, which consisted of scenarios and guided questions, were used during a 10-week teaching. Comparing students’ performances based on two tests showed that there was a significant difference between the mean performance of the PBL group and that of the conventional group – indicating PBL efficacy.